OPTIMALISASI KOMPETENSI PEDAGOGIK GURU SEBAGAI SARANA PENGUATAN KARAKTER SISWA MELALUI KEGIATAN PEMBELAJARAN DI SDN TUIS II KABUPATEN TANGERANG - Jati Purnama Achmad; Euis Rahmawati; Reksa Adya Pribadi (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2022)
Competence is the ability to a task, skills, attitudes, and all activities needed to support a success. Through optimizing pedagogic competence, it is hoped that teachers will be able to build an optimal learning experience by making a learning process a means of strengthening character through these learning activities. The purpose of this study was to determine how the process of strengthening student character through the implementation of teacher pedagogic competence and how the results of optimizing and implementing teacher pedagogic competence on student character. In the implementation of this research using qualitative methods with descriptive research type. The data collection method used in this study uses the method of observation and interviews. Furthermore, data reduction, data presentation and verification are carried out as steps in data analysis techniques. From the results of the study, it was found that the results of optimizing and implementing the teacher's pedagogical competence on the student's character were good where students experienced changes in receiving material from the teacher, students understood more and started to apply good character, students were more orderly during learning activities, and students showed a sense of obedience against school rules.